2007
DOI: 10.1590/s1413-81232007000300019
|View full text |Cite
|
Sign up to set email alerts
|

The Chernobyl accident 20 years on: an assessment of the health consequences and the international response

Abstract: Twenty years after the Chernobyl accident the WHO and the International Atomic Energy Authority issued a reassuring statement about the consequences. Our objectives in this study were to evaluate the health impact of the Chernobyl accident, assess the international response to the accident, and consider how to improve responses to future accidents. So far, radiation to the thyroid from radioisotopes of iodine has caused several thousand cases of thyroid cancer but very few deaths; exposed children were most su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…For comparison, the exposed populations had a background occurrence of millions of cancer deaths and much larger natural radiation exposures over the same period. Nevertheless, the chaotic initial response, uncertainties in dose reconstruction, and incomplete health data collection have left many questions unanswered (13,49,86,149,183).…”
Section: Nuclearmentioning
confidence: 99%
“…For comparison, the exposed populations had a background occurrence of millions of cancer deaths and much larger natural radiation exposures over the same period. Nevertheless, the chaotic initial response, uncertainties in dose reconstruction, and incomplete health data collection have left many questions unanswered (13,49,86,149,183).…”
Section: Nuclearmentioning
confidence: 99%
“…In part, fears about contamination were fueled by local doctors who indiscriminantly attributed many medical problems to radiation exposure or diagnosed patients with radiophobia 17. At the 20th anniversary, the Chernobyl Forum 24 and others 25 concluded that mental health was the biggest public health effect from Chernobyl. Although misconstrued by many to mean that the physical health effects of Chernobyl were inconsequential, the Forum report used this finding to promote the importance of integrated mental and physical health care.…”
mentioning
confidence: 99%
“…Contamination following nuclear accidents has raised public and scientific concern about pathways of exposure, the time frame of risk, and the contribution of radionuclides to population rates of developmental disorders and cancer (Cardis, 1996). Unfortunately, most estimates of the health risks of radiation exposure are derived from large, acute, external doses received by adult survivors of atomic bombs in Hiroshima and Nagasaki (Baverstock and Williams, 2006; Farilie, 2009) or during or immediately after the explosion of the Chernobyl nuclear reactor (Ivanov et al, 2001; Mück et al, 2002; Pröhl et al, 2002). These might not be applicable to low‐dose, internal, chronic exposure or to potential health effects across the lifespan (especially in utero) (Fairlie, 2009).…”
Section: Selected Birth Defectsa and Prevalence (Per 10000 Live Birtmentioning
confidence: 99%